Jewhooing the sixties : American celebrity and Jewish identity ; Sandy Koufax, Lenny Bruce, Bob Dylan, and Barbra Streisand - Kaufman, David, 1959- (Waltham, Mass. : Brandeis University Press, 2012)
A lively look at four major Jewish celebrities of early 1960s America, who together made their mark on both American culture and Jewish identity.
Introduction: Jews, celebrity, and the early 1960s -- Sandy Koufax: super Jew -- Lenny Bruce: dirty Jew -- Bob Dylan: wandering Jew -- Barbra Streisand: Hollywood Jew -- Epilogue: Jewhooing into the twenty-first century.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Nineteen sixties; Popular culture -- United States -- History -- 20th century; Jews in popular culture -- United States; Jewish entertainers -- United States; Jewish athletes -- United States; Jews in the performing arts -- United States; PERFORMING ARTS -- Reference; Jewish athletes; Jewish entertainers; Jews in popular culture; Jews in the performing arts; Nineteen sixties; Popular culture; United States; SOCIAL SCIENCE / General; 1900-1999; Electronic book; Electronic books; History